Physicochemical Parameters and Selected Heavy Metals in Water and Sediments in the Mangrove Forest at Akodo-Ise, Lagos State, Nigeria - Z. T. Agathe; A. O. Raji; K. L. Njoku; K. D. B. Attouman; A. A. J. Obima (Journal of Applied Sciences and Environmental Management)
This study provided an insight into the more recent state of mangroves located in an economic agglomeration, highlighting the evolution of ecological dimensions and their resilience in perpetual movement with human development. The objective of this paper is to assess some physicochemical parameters and selected heavy metals in water and sediments in the mangrove forest during a rainy season at Akodo-Ise, Lagos State, Nigeria using standard procedures.  Data obtained reveals that water quality parameters range from 6.76 to 7.38 [pH], 26.80°C to 27.70°C [temperature], and 1.70 to 7.60 ‰ [salinity]. Heavy metals concentrations (mg/kg) ranged from (0 to 215.80) for Pb, (0) Cd, (733.10 to 4061) Fe, (1.58 to 3.50) Cu, (3.50 to 95.10) for Ni. The trends in heavy metals concentration are complex. The sampling point and depth could influence the concentration while surrounding activities are the main factors contributing to the variation in concentration. To address the challenges, an in-depth study of the ecosystem dynamics of mangroves in the region is crucial to ensure its sustainable management. The identification and categorisation of the animal species present in the ecosystem are vital for future conservation by providing baseline data on animal diversity in the region.